Cytotoxic Effect of Lactobacillus gasseri Concentrated Filtrate on some Tumor Cell Lines in vitro - Salih, Shahlaa M; Zedan, Tamara H; Ghareeb, Abdulameer M (Al-Nahrain Journal of Science, 2018)
This study was designed to investigate the cytotoxic effect of Lactobacillus gasseri concentrated filtrate on tumor cell lines. Lb. gasseri was grown in de Mann, Rogosa and Sharp MRS broth medium and incubated anaerobically at 37ºC for 24 hrs. The culture was centrifuged and the supernatant was taken and sterilized by filtration. One hundred ml of filtrate was concentrated by oven at 40-45 ºC to three- fold (12.5 ml) and different concentrations (125, 250, 500, and 1000) µg/ ml were applied on RD, Hep-2, and AMN-3 tumor cell lines and normal cell line REF and incubated at 37ºC for 24 hrs. Results showed that the growth of RD and HepG2 were significantly inhibited (p ≤ 0.05) at125 µg/ ml of filtrate and the percentage of growth inhibition was (91.9 and 86.4)% respectively. The effect was dose-dependent and accordingly 1000µg/ ml recorded the highest percentage of growth inhibition, which was 27.8% on AMN-3 cells and 32.1% on REF cell line.